Tourism in a warming world: understanding the coolcation trend in Northern Europe - Fernández-Villarán Ara, Asunción; Rivera García, Jorge; Pastor Ruiz, Ricardo (Competitiveness Review, 2026)
Purpose This paper aims to examine the growing trend of “coolcation” holiday travel toward cooler destinations, as a response to rising global temperatures and changing tourist preferences. It analyses how destination management organizations (DMOs) in Northern Europe conceptualize and engage with this phenomenon to enhance competitiveness, sustainability and climate resilience. Design/methodology/approach The research adopts a qualitative approach, drawing on 11 email interviews, with semi-structured follow-ups (Zoom or email) conducted in selected cases for clarification, with representatives from national, regional and local DMOs across Nordic countries. A thematic content analysis was applied to identify key narratives, strategic responses and institutional constraints related to coolcation. Findings Findings reveal that while national DMOs have begun integrating coolcation into branding and sustainability narratives, regional actors approach it more cautiously, often without explicitly using the term. Coolcation is recognized as a tool for extending tourism seasons, diversifying offerings and appealing to climate-conscious travelers, but its operationalization remains uneven and underdeveloped. Practical implications Coolcation offers a strategic opportunity to rebalance tourism flows, relieve pressure on overheated and overcrowded destinations, and support economic and environmental sustainability in cooler regions. As the tourism industry faces increasing climate uncertainty, coolcation presents a timely and promising approach to future-proof destination planning and policy. Originality/value This paper introduces coolcation as an emerging adaptive strategy in tourism, bridging theory and practice by linking a market-driven travel trend with frameworks on climate adaptation, destination competitiveness and sustainable tourism development.
Keywords: coolcation; DMO; rising global temperatures; nordic destinations; making sense framwork